The American Labor Movement. A syllabus for study classes. [Forew. by S.M., Jr.] (The Workers Education Bureau Press, 1927)
Facsimile reprint: New York, Arno Press & The New York Times, 1970. (American labor. From conspiracy to collective bargaining. Advisory editors: L. Stein and Ph. Taft). In: Wages, hours, and strikes: ...